Method for Detecting Water Content of Comb-shaped Capacitor Electrode Coating - Hu, Xiang; Zhang, Aihua; Wang, Junqin (2021 International Conference on Artificial Intelligence and Electromechanical Automation (AIEA), 2021)
Rapid and non-destructive testing method carries great significance for the detection of water content in electrode coating. Based on the planar comb capacitance method, this paper develops a water content detection capacitance sensor for comb-shaped electrode coating, analyzes the detection structure and working principle of comb-shaped capacitance sensor, uses MAXWELL software to simulate the actual conditions, and finally determines the basic parameters of moisture sensor for comb-shaped capacitance electrode coating. By measuring the coating water content of low-hydrogen alkaline electrode J707 with two different sizes, the correlation between the capacitance value of the comb-shaped capacitance sensor and the coating water content is studied. The results show that the theoretical analysis is in good agreement with the results measured by the comb-shaped capacitance sensor; when the coating water content is less than 2.3%, coating water content presents a relatively good linear relationship with the capacitance value of the comb-shaped sensor. It is feasible to determine the water content of the electrode coating by detecting capacitance value of the electrode coating, and the sensor detection accuracy and error meet the requirements of engineering applications.